Unsuccessful Acupuncture Conversion of Breech Presentation - Vuković-Bobić, M.; Habek, D. (Geburtshilfe und Frauenheilkunde, 2006)
A case is presented of fetal oblique position with compound presentation, where acupuncture conversion of breech presentation failed due to the umbilical being wrapped three times around the fetus with a knot in the umbilical cord, so that delivery was terminated by cesarean section. Conversion of the fetal breech presentation was induced by manual acupuncture stimulation of the UB 67 acupoint with simultaneous CTG control in the 35th week of pregnancy. During the first acupuncture stimulation, CTG showed protracted uterine contraction with subsequent regular low amplitude contractions with intensified fetal activity and CTG curve reactivity. In the 39th week of gestation, the patient felt regular contractions verified by CTG records showing reactive curves. Obstetrical examination revealed a cervical dilatation of 4 cm, a compound presentation involving both legs and the umbilical cord, and oblique position. Therefore, a cesarean section according to a modified Misgav-Ladach method was performed and the patient gave birth to a healthy male neonate (3330 g, 49 cm, Apgar 10/10, pH 7.334). The obstetrician should warn the patient of the potential risks and complications associated with any method of breech presentation conversion.
Keywords: Beckenendlage; Akupunktur